FORMULATION AND EVALUATION OF IN VITRO TRANSDERMAL PATCH DICLOFENAC SODIUM USING CHITOSAN POLYMER AND POLYVINYL ALCOHOL CROSS-LINKED TRIPOLYPHOSPHATE SODIUM - GINTING, ERNAWATY; Reveny, Julia; Sumaiyah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to investigate diclofenac sodium patches using chitosan (Ch) and polyvinyl (PVA) alcohol cross-linked tripolyphosphate sodium (TPP) to increased transdermal permeation of the drug from the matrix system across rabbit skin. Materials and Methods: The chemical characterization of diclofenac sodium was done by ultraviolet-visible spectrophotometry. Formulation of diclofenac sodium patches using solvent evaporation method with cross-link technique. Evaluation of physical character of the film includes organoleptic observation, weight test, thickness, % moisture absorption, fold resistance, interaction between materials used Fourier transform infrared (FTIR), and active substance levels. The drug release was determined using Franz diffusion cells in phosphate buffer (pH 7.4). Results: The result of physiochemical parameters of the transdermal patch were found satisfactory. Formula F1, F2, F3, and F4 produce patches with fine texture, F5 and F6 formulas produce patches with coarse texture. Formula F1, F2, F5, and F6 are flexible and fulfill the multiplier test requirements, while the F3 and F4 formulas are not flexible and do not meet the multiplier test requirements. The patch weight, thickness, and drug content were uniform. The release of patches with following the zero-order release. The optimal formula with the total sodium diclofenac released as much as 17.89 Î¼g, the release flux of 89.42 Î¼g/cmÂ²/h of permeation time of 10 h and the moisture absorption rate of 1.07Â±0.193. The FTIR data of rabbit skin indicated Ch and PVA alcohol cross-linked TPP increase transdermal permeation of diclofenac sodium in the stratum corneum. Conclusion: The diclofenac sodium can be prepared by cross-linked method, resulted in a better discharge profile.